Cultures of collaboration in engineering design education: a contrastive case study in France and Japan. Issue 1 (3rd April 2017) - Détienne, Françoise; Baker, Michael; Vanhille, Mohini; Mougenot, Céline
Abstract: Engineering students need to learn to collaborate, to create and to innovate in culturally diverse socio-organisational contexts. However, research on intercultural differences provides results that are not specifically grounded in collaborative and creative engineering education practices. This paper presents a contrastive case study of engineering students' appraisals of the quality of collaboration in collaborative design situations. Based on an extended multidimensional appraisal method (called 'QC2'), we contrasted French and Japanese engineering students' appraisals of: (1) ideal collaboration in design; (2) quality of collaboration with respect to actual cases of collaborative design in France and in Japan (as shown on videos). Results showed a common French–Japanese culture of collaboration across the engineering students with respect to aspects of design relating specifically to the domain of engineering, yet differences with respect to appraisals of dimensions of group work (task/group orientation and argumentation). These results, of a detailed situated case study, are compared with results of (mostly questionnaire-based) research on general cultural differences. We conclude with prospects for elaborating an operational trans-cultural concept of institutional culture of collaboration, and implications for training engineering students, especially for multicultural collaboration.